Determining the Prevalence and Predictors of Non-Uptake of HIV Voluntary Counselling and Testing among Undergraduates of Tertiary Institution in Abia State, Nigeria - Onyemachi, Prince Ezenwa N.; Awa, Madu James; Ejikem, Mazi E. C.; Enukeme, Juliet U. (Disease and Health Research: New Insights Vol. 3, 2024)
Background: One of the key strategies in the HIV/AIDS prevention and control programmes in Nigeria is Voluntary HIV counselling and testing (VCT). There were 38 million people living with HIV/AIDS globally at the end of 2019 with an estimated 1.7 million new infections, declining by 23% from the 2010 value of 2.1 million. However, its utilisation among young adults, particularly undergraduates, is very low. Due to the dearth of data on the subject in the study area, the aim of the present study was to determine the prevalence and predictors of non-uptake of VCT among undergraduates. Methods: The study was conducted at Abia State University, which is one of the state-owned universities, located in South East part of Nigeria. A cross-sectional study using quantitative methods was conducted. Using a multistage sampling technique, three faculties were selected out of nine, and 422 respondents were selected from three faculties. Interviews were conducted by trained enumerators with validated, pre-tested, semi-structured questionnaires. Data analysis was done using a statistical package for social sciences version 20. Prevalence was measured by the percentage of respondents who had never used VCT. Analytical statistics were done using a chi-square test to measure the strength of the association between VCT uptake and the knowledge and attitude of respondents. Association with a P-value < 0.05 was considered significant. Logistic regression was used to identify predictors of non-uptake of VCT. The associations were presented as odds ratios (OR) and 95% confidence intervals. Results: A total of 237 (59.3%) respondents were knowledgeable about VCT while the majority, 259 (64.7%) had a negative attitude towards it. Knowledge (X2 = 9.89, P-value < 0.001) and attitude (X2 = 10.78, P-value < 0.001) showed a statistically significant association with VCT uptake. The prevalence of non-uptake of VCT among the respondents was 82.7%. Ignorance, fear of positive tests, stigma, and discrimination were found to be strong predictors of non-uptake of VCT. OR 1.874 (1.058 - 3.289), P < 0.001; OR 2.455 (1.308 - 4.608), P < 0.000 and OR 2.318 (1.299 - 4.128), P < 0.000 respectively. This study showed that the majority of the respondents generally had good knowledge of VCT for HIV with the majority also knowing that it is voluntary. Conclusions: Voluntary counselling and testing uptake among undergraduates was low and determined by VCT-related ignorance, poor attitude, fear of positive results, and HIV/AIDS-related stigma/discrimination. The implication of the findings for HIV prevention and control efforts in Nigeria lies in the importance of addressing the identified predictors of non-uptake of VCT. Further, strengthening the communication between VCT clinics and other local community and health services is also an indispensable strategy for deepening awareness about VCT, mitigating stigma, and enhancing uptake. It is also imperative to target specific interventions at high-risk and vulnerable young adults, particularly in tertiary institutions, when designing, expanding, and implementing VCT services by stakeholders in the country.